PERANCANGAN ULANG DAN OPTIMALISASI INFRASTRUKTUR JARINGAN KOMPUTER MENGGUNAKAN METODE NDLC DI MAN 5 TASIKMALAYA - Ardi Al ansori; Ghani Rizki Ferrari; Helmy Dzulfikar (Journal of Information System, Informatics and Computing, 2026)
This study redesigns the network infrastructure of MAN 5 Tasikmalaya using the NDLC method to resolve traffic congestion during peak exam hours caused by the use of HUBs in 12-15 classrooms. The primary issue of collision domains was confirmed through Wireshark analysis, which identified packet retransmissions, and nPerf testing, which showed a low browsing score of 56.43% despite a 129.21 Mbps capacity. To address this, the architecture was upgraded to an Extended Star topology by replacing HUBs with Managed Switches and implementing bandwidth management via MikroTik (Simple Queue and hotspot cookies). Validation through Cisco Packet Tracer confirmed successful connectivity across all segments, concluding that eliminating collision domains and optimizing traffic significantly improves network stability and quality of service.